Islamic Boarding School Management System In Increasing The Competitiveness Of Islamic Boarding Schools In Jambi Province - Tabroni Tabroni; A. Husein Ritonga; Kasful Anwar Us (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research presents the management system of Islamic boarding schools in increasing competitiveness in Jambi province. This research, which uses a qualitative approach with observation, interview and documentation techniques, was conducted at Pondok Karya Pembangunan Al-Hidayah Jambi, Pondok Pesantren Sheikh Maulana Qori Bangko, and Pondok Pesantren Zulhijjah in Muara Bulian. The results of this study that the Islamic Boarding School Management System in increasing competitiveness (1) The Sheikh Maulana Qori Bangko Islamic Boarding School conducts first, the formation of a good Islamic boarding school organizational structure Second, the formation of a working meeting at the beginning of the year. The working meeting is directly led by the Kiai of the boarding school. Third, the plenary meeting discusses the determination of the work procedures of the board of students, establishing a work program. Fourth, planning the realization of the boarding school management system program (2) Karya Pembangunan Al-Hidayah Jambi boarding school, namely conducting stage I organizational decision objectives, Stage II formulating the current situation, Stage III identifying facilities and obstacles and Stage IV developing a series of activities (3) Pesantren Zul Hijjah Muaro Bulian formed a pesantren academic development team. Then the team analyzed the pesantren. The team then held a meeting to determine efforts to increase the potential and efforts to improve the boarding school